A proposed simplified scorecard for the linear descriptive evaluation of dairy characters of female camels (Camelus dromedarius) of the Majaheem breed - Dioli, Maurizio; Nasef, Mostafa; Braithwaite, Bruce James; Rehman, Umar (Frontiers in Animal Science, 2023)
The camel (Camelus dromedarius) holds significant importance as a valuable livestock species for milk production. Consequently, there is an increasing need to enhance attitudes towards increasing camel milk production by selectively breeding camels with desirable milk production attributes.Majaheem camels have gained recognition for their favorable milk production traits. However, there is currently a lack of rational and modern tools to aid in the evaluation of Majaheem camels specifically for their milk production capabilities. To address this deficiency and provide guidance to camel breeders in effectively evaluating and selecting superior milk-producing Majaheem camels, a breed linear scorecard is proposed in line of what is adopted for Holstein Frisian milking cattle but simplified and adapted to the phenotypic characteristics of the Majaheem camel breed.